Jichihan and the Restoration and Innovation of Buddhist Practice - Buijnsters, Marc (Japanese journal of religious studies, 1999)
The various developments in doctrinal thought and practice during the Insei and Kamakura periods remain one of the most intensively researched fields in the study of Japanese Buddhism. Two of these developments concern the attempts to restore the observance of traditional Buddhist ethics, and the problem of how Pure Land tenets could be inserted into the esoteric teaching. A pivotal role in both developments has been attributed to the late-Heian monk Jichihan, who was lauded by the renowned Kegon scholarmonk Gy6nen as "the restorer of the traditional precepts" and patriarch of Japanese Pure Land Buddhism. " At first glance, available sources such as Jichihan's biographies hardly seem to justify these praises. Several newly discovered texts and a more extensive use of various historical sources, however, should make it possible to provide us with a much more accurate and complete picture of Jichihan's contribution to the restoration and innovation of Buddhist practice.